2016
DOI: 10.1126/science.aaf1064
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 is required for proper macrophage and microglial function in mice

Abstract: Expansions of a hexanucleotide repeat (GGGGCC) in the noncoding region of the C9orf72 gene are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. Decreased expression of C9orf72 is seen in expansion carriers, suggesting loss of function may play a role in disease. We find that two independent mouse lines lacking the C9orf72 ortholog (3110043O21Rik) in all tissues developed normally and aged without motor neuron disease. Instead, C9orf72 null mice developed progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
540
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(618 citation statements)
references
References 35 publications
48
540
3
1
Order By: Relevance
“…However, zebrafish models show reduced axon length in motoneurons and reduced locomotion after antisense morpholino-mediated reduction of C9ORF72 levels 5 . In contrast to the results in C. elegans and zebrafish, studies in mouse have so far not revealed conclusive results for C9ORF72 loss of function as a possible cause of FTLD/ALS [13][14][15][16] . Administering antisense oligonucleotides (ASOs) targeting mouse C9ORF72 by stereotactic intracerebroventricular (ICV) injection reduced C9ORF72 mRNA levels to 30-40% of control levels in the spinal cord and brain 17 .…”
Section: C9orf72 Interaction With Cofilin Modulates Actin Dynamics Inmentioning
confidence: 65%
“…However, zebrafish models show reduced axon length in motoneurons and reduced locomotion after antisense morpholino-mediated reduction of C9ORF72 levels 5 . In contrast to the results in C. elegans and zebrafish, studies in mouse have so far not revealed conclusive results for C9ORF72 loss of function as a possible cause of FTLD/ALS [13][14][15][16] . Administering antisense oligonucleotides (ASOs) targeting mouse C9ORF72 by stereotactic intracerebroventricular (ICV) injection reduced C9ORF72 mRNA levels to 30-40% of control levels in the spinal cord and brain 17 .…”
Section: C9orf72 Interaction With Cofilin Modulates Actin Dynamics Inmentioning
confidence: 65%
“…Moreover, increased activated circulating macrophages, abnormal numbers of CD4 T‐cells, antibodies and circulating immune complex have been described in blood of ALS patients, but the results have been inconsistent 70, 71. Interestingly, the development of C9orf72 null mouse models, after identification of a mutated version of this gene in a significant proportion of ALS patients, did not lead to overt motor impairment 72, 73. Instead, an array of peripheral immune organ abnormalities arose, including splenomegaly, lymphadenopathy and eventually an autoimmune‐like phenotype 72, 73.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 99%
“…Interestingly, the development of C9orf72 null mouse models, after identification of a mutated version of this gene in a significant proportion of ALS patients, did not lead to overt motor impairment 72, 73. Instead, an array of peripheral immune organ abnormalities arose, including splenomegaly, lymphadenopathy and eventually an autoimmune‐like phenotype 72, 73. Nonetheless, macrophages and microglia appeared particularly susceptible, showing lysosomal dysfunction and a proinflammatory state 73.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 99%
See 1 more Smart Citation
“…However, several mouse models with a general or neuron-specific deletion of C9orf72 did not develop clinical or pathological signs of motor neuron disease [2,27,28,35,42]. Instead, some models developed splenomegaly, lymphadenopathy, auto-immune disorders and neoplastic events, indicative of a primary role of the C9orf72 protein in immunity [2,35,42]. Interestingly, the C9orf72 protein has been shown to be a key player in regulation of autophagy [49].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%